Paraoxonase-1 activities and procalcitonin levels in sepsis and non-infectious systemic inflammatory response syndrome patients in a tertiary intensive care unit - Alias, Mohd Afzal; Abdullah, Nor Zamzila; Mat Nor, Mohd Basri; Md Ralib, Azrina (IIUM Press, International Islamic University Malaysia, 2017)
Sepsis and septic shock remain to be a leading cause of death in the intensive care unit (ICU), including in Malaysia. Distinguishing early sepsis from non-infectious systemic inflammatory response syndrome (SIRS) may be difficult upon presentation. Thus, research has been ongoing in finding a specific and effective marker for sepsis, where paraoxonase-1 (PON1) has shown to be a promising contender. PON1 is a high density lipoprotein associated enzyme, where early researches have shown that its activities decrease as oxidative stress increases in intensity during sepsis. This study aimed to compare PON1 activities between sepsis and non-infectious SIRS patients, as well as comparing its activities in patients who ultimately survived or died as a result of their ordeal. In addition, this study looked into the diagnostic and predictive performance of PON1 for sepsis and mortality as well as the correlation between PON1 activities and a known sepsis marker, procalcitonin (PCT). This prospective observational study, recruited ICU patients above the age of 18 with SIRS and divided them into sepsis and non-infectious SIRS based on clinical assessment with or without positive cultures. PON1 activities; paraoxonase (PON) and arylesterase (ARE) activities, and PCT levels were measured daily over the first three days of ICU admission. Out of the 239 patients recruited, 164 (69%) had sepsis and 68 (28.5%) died in hospital. Results showed significantly lower PON1 activities in sepsis compared to non-infectious SIRS throughout the three-day. PON1 activities were also significantly lower in non-survivors compared to the survivors Further analysis also showed that ARE activity to be a slightly better detector of sepsis than PON activity (PON AUC 0.64-0.65 versus ARE AUC 0.67-0.69), but similar in power in predicting mortality (ARE AUC 0.61-0.64, PON AUC 0.62-0.64). PON1 activities and PCT levels were all significantly correlated with weak to moderate correlation with r-values between 0.207- 0.476. We concluded that PON1 activity measured early on ICU admission has a big potential to be a biomarker in distinguishing sepsis from non-infectious SIRS and in prediction of mortality. A larger scale study, involving multiple centres could be done to further confirm or refute these findings.